Radiation exposure in endovascular stroke treatment of acute basilar artery occlusions: a matched-pair analysis - Weyland, Charlotte S.; Potreck, Arne; Neuberger, Ulf; Möhlenbruch, Markus Alfred; Nagel, Simon; Ringleb, Peter A.; Bendszus, Martin; Pfaff, Johannes (Neuroradiology, 2020)
To determine the radiation exposure in endovascular stroke treatment (EST) of acute basilar artery occlusions (BAO) and compare it with radiation exposure of EST for embolic middle cerebral artery occlusions (MCAO).
Gesehen am 09.12.2021